BIOGENIC SYNTHESIS AND CHARACTERIZATION OF SELENIUM NANOPARTICLES USING CYANOBACTERIAL SPECIES AND ITS ANTI-BACTERIAL ACTIVITY - PADHIARY, ARCHANA; MIR, SHOWKAT AHMAD; PATI, AISWARYA; TETE , SHEARY SOMAM; NAYAK, BINATA (The Bioscan, 2023)
The biogenic potential of two fresh water cyanobacterial sp. (Anabaena UU2493, Calothrix UU24112) and two marine water cyanobacterial sp. (Lyngbya BDU72401 and Phormidium BDU7060) are used to synthesize selenium nanoparticles. The characterization of synthesized selenium nanoparticles was done using UV-VIS spectroscopy, TEM, FTIR, and X-RD. The X-RD data revealed that freshwater cyanobacterial species synthesize amorphous SeNPs, whereas, marine water cyanobacterial species synthesize SeNPs in crystalline form. The functional groups involved in the bio-reduction of selenium nanoparticles were monitored by FTIR spectroscopy. The synthesized SeNPs in combination with chloramphenicol (100ug/ml, 200ug/ml, 300ug/ml and 400ug/ml) against E. coli MG1655 were evaluated and the SeNPs synthesized by Calothrix UU24112 showed higher antibacterial activity. The synthesized SeNPs by Calothrix UU24112 were assessed for photo catalytic dye degradation, safranin and crystal violet activity through UV-Vis irradiation techniques and play a pivotal role in photocatalytic activity.